2016
DOI: 10.1103/physrevlett.116.226402
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Metamagnetic Quantum Criticality inSr3Ru2O7

Abstract: Bilayer strontium ruthenate Sr 3 Ru 2 O 7 displays pronounced non-Fermi liquid behavior at magnetic fields around 8 T, applied perpendicular to the ruthenate planes, which previously has been associated with an itinerant metamagnetic quantum critical end point (QCEP). We focus on the magnetic Grüneisen parameter Γ H , which is the most direct probe to characterize field-induced quantum criticality. We confirm quantum critical scaling due to a putative two-dimensional QCEP near 7.845(5) T, which is masked by tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
4
23
1
Order By: Relevance
“…This has been proposed for the bilayer strontium ruthenate Sr 3 Ru 2 O 7 [28]. Very recently a careful study of the magnetic Grüneisen parameter has revealed that this material actually realizes a more complicated scenario, with two subsequent field-induced QCPs (for the critical fields see Table 1) [12]. The Γ H data also allowed to determine scaling regimes associated with both QCPs and the phase space where scaling fails due to the interference of both instabilities.…”
Section: Finite-induced Quantum Criticalitymentioning
confidence: 87%
See 1 more Smart Citation
“…This has been proposed for the bilayer strontium ruthenate Sr 3 Ru 2 O 7 [28]. Very recently a careful study of the magnetic Grüneisen parameter has revealed that this material actually realizes a more complicated scenario, with two subsequent field-induced QCPs (for the critical fields see Table 1) [12]. The Γ H data also allowed to determine scaling regimes associated with both QCPs and the phase space where scaling fails due to the interference of both instabilities.…”
Section: Finite-induced Quantum Criticalitymentioning
confidence: 87%
“…The Grüneisen parameter diverges upon approaching the QCP at r = 0 following T −1/(νz) or respectively at T = 0 according to r −1 with universal prefactor G r = ν(d − z) [1,2]. Such divergences have been found in magnetic Grüneisen parameter measurements on various strongly correlated electron systems in recent years, which are listed in Table 1 [8,9,[11][12][13][14][15][16][19][20][21][22][23]. The table does not include low dimensional spin systems for which the magnetic Grüneisen parameter has been investigated experimentally and theoretically near field-induced quantum phase transitions [24][25][26].…”
Section: Introductionmentioning
confidence: 95%
“…This scaling is distinct from the Kadowaki-Woods relation A ∼ γ 2 (24), which instead follows from the resistivity ρ ∝ m 2 h T 2 . Microscopically, the mass enhancement has been assumed to be tied up with metamagnetic quantum criticality of the hot electrons (2,(25)(26)(27). The results above are not sensitive to the details of these physics beyond requiring a divergent m h in a small region of the Brillouin zone.…”
Section: Low-temperature Approach To the Critical Fieldmentioning
confidence: 98%
“…Careful analysis 12 reveals a power law divergence of C/T as a function of reduced field h = (H − H C )/H C with an unexpected exponent of -1. It has been suggested that the singularities in C/T as a function of field or temperature are consistent with a 2D metamagnetic QCEP within the canonical description of quantum criticality 13 . The expected exponent within this theoretical framework is -1/3 and in general has to be fixed in any fit of this model 14 exponent of -1 in an assumption-free power law fit to C/T therefore raises the important question of whether the current theoretical understanding is incomplete.…”
mentioning
confidence: 92%